Pulp Calcification: Case reports with difficult Endodontic Problem - Haque, Sabrina; Hossain, Md Zakir (City Dental College Journal, 2012)
Teeth with signs and symptoms with calcified pulp require treatment. If it is possible to introduce endodontic instrument into the canal, conventional root canal treatment is done. In cases where root canal treatment is not possible, surgical approach may be necessary [6]. In calcified canals, instrumentation is attempted very carefully because there often remains very fine pathway within the calcified materials. Once a fine file (no. 06) has reached the correct level, enlargement of the canal is a simple matter. Use of EDTA alone or RC preparation along with NaOCl irrigant will often help this stage of the operation. If instrumentation is not possible, one should use an engine driven instrument to grind away the stone with small round, long shanked burs. In symptomless tooth with calcification, no treatment is required. Such a tooth should be kept under yearly radiographic review, and if symptoms arise may best be treated surgically [1]. DOI: http://dx.doi.org/10.3329/cdcj.v9i1.11833 City Dental College Journal Vol.9(1) 2012 19-22